Do Political Parties Matter? - Evidence from German Communities - Christian Wittrock; Nadine Riedel; Martin Simmler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The paper aims to test whether partisanship affects policy outcomes at the local level. While the literature has presented comprehensive evidence for partisan effects on policy outcomes at the state and federal level, recent findings suggest that partisan effects may be absent at the city and municipality level. Using detailed data on public goods and service spending, we assess the link between the partisanship of local councils and the composition of public good spending of German localities. Firstly, we estimate panel data models assessing whether changes in partisanship impact per-capita-spending in different spending-categories. Secondly, we investigate whether left-wing or right-wing communities differ in their spending response to exogenous revenue shocks during their legislative term (among others induced by changes of the personal income tax base assigned to communities). Using propensity score matching and weighting, the approach compares responses in comparable municipalities, which differ in the partisan composition of their local council. Based on both strategies, we find moderate partisan effects only.
Keywords: H70; H40; R50; 330